2013
DOI: 10.1016/j.ygyno.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mitotic cell death by overriding G2/M checkpoint in endometrial cancer cells with non-functional p53

Abstract: Objective Endometrial tumors with non-functional p53, such as serous uterine endometrial carcinomas, are aggressive malignancies with a poor outcome, yet they have an Achilles’ heel: due to loss of p53 function, these tumors may be sensitive to treatments which abrogate the G2/M checkpoint. Our objective was to exploit this weakness to induce mitotic cell death using two strategies: (1) EGFR inhibitor gefitinib combined with paclitaxel to arrest cells at mitosis, or (2) BI2536, an inhibitor of polo-like kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 38 publications
4
48
1
1
Order By: Relevance
“…The increased metastases in some of these animal models may be in part due to the activation of the EGFR/PI3K/AKT pathway [82,92]. These data are consistent with a previous study by our group in which inhibition of EGFR only synergized with chemotherapy in the absence of R175H p53 [91]. In addition to new protein interactions, the R175H mutant is capable of binding DNA and inducing direct transcriptional changes that can create a pro-survival and chemoresistant phenotype.…”
Section: Oncomorphic P53 Mutationssupporting
confidence: 89%
See 1 more Smart Citation
“…The increased metastases in some of these animal models may be in part due to the activation of the EGFR/PI3K/AKT pathway [82,92]. These data are consistent with a previous study by our group in which inhibition of EGFR only synergized with chemotherapy in the absence of R175H p53 [91]. In addition to new protein interactions, the R175H mutant is capable of binding DNA and inducing direct transcriptional changes that can create a pro-survival and chemoresistant phenotype.…”
Section: Oncomorphic P53 Mutationssupporting
confidence: 89%
“…In experiments in lung cancer cells devoid of p53, overexpression of the oncomorph R175H p53 enhances resistance to both etoposide and cisplatin [40]. Furthermore, our studies indicate that expression of R175H p53 in endometrial cancer cells mediates resistance to paclitaxel in a mechanism that involves maintenance of the G2/M checkpoint [91]. …”
Section: Oncomorphic P53 Mutationsmentioning
confidence: 86%
“…Third in frequency, mutations at R175 have been shown to mediate resistance to etoposide and cisplatin in lung carcinoma cells and to paclitaxel in endometrial carcinoma cells [25,32]. We did not observe any significant in vitro results related to R175, and survival of TCGA patients with R175 mutations was not significantly different than the general cohort of patients with a TP53 mutation.…”
Section: Discussioncontrasting
confidence: 61%
“…Using p53-null endometrial tumors as a model system, we found that gefitinib produces a synergistic enhancement of the inhibitory action of paclitaxel in p53-inactivated endometrial cancer cells [97]. In p53-null cells, the G2/M checkpoint is maintained through an alternate pathway that includes activation of p38 MAPK/MK2, which results in inactivating phosphorylation of cdc2.…”
Section: Use Of Her-targeted Inhibitors In Gynecologic Cancersmentioning
confidence: 99%
“…In p53-null cells, the G2/M checkpoint is maintained through an alternate pathway that includes activation of p38 MAPK/MK2, which results in inactivating phosphorylation of cdc2. Mechanistic studies revealed that treatment with gefitinib in combination with paclitaxel overcomes this checkpoint to reduce cdc2 phosphorylation [97]. All cells are shifted into M phase, where they are sensitive to paclitaxel and undergo mitotic catastrophe.…”
Section: Use Of Her-targeted Inhibitors In Gynecologic Cancersmentioning
confidence: 99%